To solve this system using substitution, we can start by rearranging the first equation to solve for y:
y = -4x - 1
Now we can substitute this expression for y in the second equation:
2(-4x - 1) + 2 = -12x
Now we can simplify and solve for x:
-8x - 2 + 2 = -12x
-8x = -12x
4x = 0
x = 0
Now we can substitute this value of x back into the first equation to find y:
y = -4(0) - 1
y = -1
Therefore, the solution to the given system is x = 0 and y = -1.
Solve the following system using substitution. What is the solution to the given system?
y = −4x −1 and 2y + 2 = −12x
=
−
4
−
1
2
+
2
=
−
12
(1 point)
Responses
1 answer